'Isn't it ironic…!?!' - mobility researchers go sedentary. A group auto-ethnography on collective coping and care in pandemic times - Martel, Kerstin; Raupp, Monique; Abdul-Hadi, Acil; Oleskeviciute, Emilija; Mello, Rodrigo; Biswas, Tania; S. Milani, Giovanna (Wiley, 2021)
We moved places and places moved us, until force majeure detained us on the spot. Signed-up to be hyper-mobile PhD-candidates, we became hyper-reflective pandemic intimates. We moved together into a space that felt safe, OUR safe space. Suspended. Did the pandemic open this door, or had this space always existed, even back in the old days? Probably the latter, although we were not sensitive enough to perceive it, too busy to push the door, too lonesome to CARE. Not attentive to its possibilities, not imaginative of its POWER, too confident to be capable of succeeding alone. Even if we might have secretly wished for this space to exist. The present piece of work, and JOY, might be described by others as a ‘side-step’, a ‘hobby project’, a “shadow activity”. For us, it is a recollection of shocks and wonders, a sentience of precious, ephemeral instances that last. We are a group of eight early career researchers who study global mobility and labour migration from a variety of disciplinary perspectives. With prior international mobility experience, we left our previous countries of residence in 2018 to join an EU-funded research project, whilst being located in different European cities. One could classify us, for example, as highly qualified, privileged migrants. The present paper is the outcome of a collaborative, auto-ethnographic study, conducted in 2020, in the midst of the Covid-19 pandemic, when we suddenly were forced not to travel anymore. We got together online every week to ‘refaire le monde,’ and we conducted virtual, dialogical self-interrogations and group reflections. Based on an emic approach, in line with Chang, Ngunjiri, and Hernandez (2013), we applied an iterative process of data collection and analysis. Our weekly conversations naturally emerged as a safe space for exchange and understanding, as we were facing similar situations, despite staying at different places. Suddenly, as the privilege of ‘always being on the move,’ ‘always socializing and networking’ disappeared due to closed borders and pandemic threats, we experienced anxieties and isolation and had to re-evaluate our perceptions on life, work, and international mobility. The very purpose and meaning of our broader research endeavors and employment perspectives suddenly faded away. We realized more than ever before, what it means to us to be allowed to move, to travel freely across continents.
Keywords: affect; belonging; global mobility; group auto-ethnography; pandemic; pandemics; fi=Henkilöstöjohtaminen|en=Human Resource Management|